Vegetation Structure and Damage Level Mangrove Forest in Manomadehe Island, Subdistrict South Jailolo, North Maluku Province - Salim Abubakar; Riyadi Subur; Masykhur Abdul Kadir; Rina Rina; Adi Noman Susanto; Hendrik Suryo Suriandjo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Mangrove forest is a natural resource typical of tropical coasts, which has multiple benefits with a very broad impact when viewed from social, economic and ecological aspects. Management of natural resources must be very prudent because it takes a long time to be able to recover when damage / extinction has occurred. The purpose of this study was to determine the composition of mangrove species, the structure of mangrove forest vegetation (species density, relative density of species, frequency of species, relative frequency of species, species cover, relative cover of species and important values) and to determine the level of damage. Extraction of mangrove vegetation using the